Synthesis of Some Substituted Imidazo Triazolyl-Thiazolidinones - Sivaram, S.D.V.N.; Parikh, K.; Shiradkar, M.R.; Chakravarthy, A.K. (Asian Journal of Chemistry, 2010)
In this paper, a series of novel clubbed imidazo triazolylthiazolidinones compounds were designed which may emerge as potential antimycobacterial agents. The synthesized compounds were characterized by IR, NMR and elemental analysis.